Theoretical and experimental evaluations of the convective and conductive heat transfers in a domestic hot-water store - Chauvet, L. P. J. (Cranfield University, 1991)
The design of a water based thermal store for use in a domestic central heating system has been investigated theoretically, experimentally and numerically. The transient operation of the store during both the space heating and domestic hot-water modes of operation have been investigated separately. Heat transfer correlations in terms of Nusselt and Rayleigh numbers have been developed in order to predict the natural convection heat transfer coefficient for the outside surface of the horizontal axis finned tube heat exchanger coil located within the store. These heat-transfer correlations can predict the value of the heat transfer coefficient with an accuracy of better than 5% and are in good agreement with existing heat transfer correlations developed for the same geometry of finned tubes and modes of heat transfer. The effect of the water flow rate in the heat exchanger coil on the internal heat transfer coefficient is also investigated. This flow rate should be above 4 litre/minute to achieve a high rate of heat-transfer from the wall of the heat exchanger to the water in the pipe. A detailed investigation of the use of horizontal and vertical baffles to increase the effectiveness of heat delivery in the domestic hot water mode has been carried out. Some improvements can be achieved by the use of a horizontal flat plate located in the middle of the store. This plate, when correctly sized enhances stratification and hence improves the effectiveness of heat recovery. Vertical plate arrangements and a rectangular duct situated around the upper heat exchanger coil were found to be ineffective. However, due to an increased velocity of the water around the heat exchanger, the external heat transfer coefficient of the heat exchanger was increased by 12%. The comparison of experimental observations with computer simulations of the development of the thermocline in the store during the space heating mode of operation showed the presence of a jet in the bottom region of the store at the return inlet. The jet induces a significant amount of mixing in the store which reduces the effectiveness of heat recovery. Correlations in terms of Richardson number and effectiveness of heat delivery have been developed to characterize the effect of this jet. An inlet arrangement designed to achieve a Richardson number exceeding 3 significantly reduces the mixing created by the jet and can increase the amount of heat delivered in the space heating mode by approximately 5%.